Development of learning material to wind power courses - Bruhn, Kristin; Lorensson, Sofia; Svensson, Jennie (My University, 2009)
Wind power plants are more and more commonly used as power production units, which lead to an increased demand of educated personnel within the area. Today, Sweden produces about 1.4 TWh wind power per year, but Sweden and EU have set goals that will increase the production enormously in the future. Difficulties occur in the education stage of wind power, since the selection of course material is poor. Investigations of wind power courses in Europe showed that Denmark is the leading country in Europe regarding wind power education. In Sweden, University Gotland has the widest range of courses in the area. This master thesis is about developing course material for education in wind power technology. It includes two compendia with appropriate learning material to achieve relevant knowledge. The compendium for upper secondary school has a basic level and is written in Swedish, the one for master students is written in English and includes one basic, and one advanced part with focus on electrical components and how to connect wind power plants to the power grid. To gather information and knowledge of what is appropriate to include in the learning material, meetings and study visits have been arranged. There have been meetings with persons in the wind power business, teachers and people in Power Cluster, a wind power project in EU. Study visits have been done at University Gotland and Vattenfall, located at Näsudden. A visit inside a wind power plant at Hönö has also been done in order to study a nacelle from the inside. The produced material in this project is only a start of the education material development, which is why there are large possibilities to develop it further in the future.
Keywords: Elkraftteknik; Electric power engineering